Effects of gender roles on legume production, utilization and complementary feeding in Dedza and Ntcheu districts of Malawi - Mulenga, Haswel (Lilongwe University of Agriculture and Natural Resources, 2018)
Child undernutrition remains one of the health challenge among rural farming households in Malawi particularly during the first two years of life. Appropriate complementary feeding practice is essential for proper growth and development of infant and young children. To effectively promote child nutrition, it is important to understand the effect of gender roles, access to and control of resources on child feeding practices. A research study was conducted in Dedza and Ntcheu with legume farming households with children aged 6-23 months who were part of the Africa RISING ‗mother trial‘ or ‗baby trials‘ for two seasons (2014/2015 to 2015/2016). The key objective of the research was to understand and assess the effect of gender roles on infant and young child feeding practices. The research targeted 291 households with children 6-23 months. Eight focus group discussions (FGDs) for in-depth qualitative data were conducted to understand the social, economic and cultural aspects of gender roles in infant and young child feeding. Two 24-hour recalls and food frequency questionnaire were used to collect data on infant and young child feeding practices while women empowerment in agriculture index (WEAI) and Harvard analysis framework were used to collect data on gender roles, activity profile, access and control over resources at household level.